Cold Chain Logistics and the Performance of Private Hospitals in Nairobi City County, Kenya - Charles, Douglas Momanyi; Nyile, Erastus (International Journal of Supply Chain and Logistics, 2026)
Purpose: Cold chain logistics has become an essential component of healthcare supply chains, particularly in the management of temperature-sensitive medical products such as vaccines, blood products, and pharmaceuticals. However, inefficiencies in cold chain systems continue to undermine service delivery and operational outcomes in private hospitals. This study examined the effect of cold chain logistics on the performance of private hospitals in Nairobi City County. Methodology: The study adopted a descriptive research design to facilitate systematic data collection and analysis. The target population comprised 429 private hospitals, from which a sample of 206 respondents was selected using simple random sampling. Primary data were collected using structured questionnaires administered to procurement managers. Data analysis involved both descriptive and inferential statistics, including correlation and regression analysis, to establish the relationship between cold chain logistics and hospital performance. Findings: The findings revealed that cold chain logistics has a positive and statistically significant effect on hospital performance. Specifically, the use of reliable refrigeration systems, temperature monitoring technologies, and specialized transport mechanisms was found to significantly reduce product wastage, improve inventory management, and enhance operational efficiency. Inferential results confirmed that cold chain logistics is a significant predictor of performance, indicating that improvements in cold chain systems lead to better service delivery and patient safety outcomes. Unique Contribution to Theory, Policy and Practice: This study contributes to the existing body of knowledge by providing empirical evidence on the role of cold chain logistics in improving healthcare performance within a developing country context.